The Prevention Research Support Program: supporting innovation in research, translation and capability building - Beth Stickney; Danielle M Campbell; Andrew J Milat; Sarah Thackway (Sax Institute, 2018)
Objectives: The Prevention Research Support Program (PRSP) is a New South Wales (NSW) Ministry of Health funding scheme. The scheme aims to build capability, and strengthen prevention and early intervention research that is important to the NSW public health system (NSW Health) and that leads to improved health and reduced health inequities for the people of NSW. This paper describes how PRSP funding has supported recipients to produce high-quality, policy-relevant research, and increase the impact of research on policy and practice. Type of program: The PRSP is a competitive funding program that supports NSW research organisations that conduct prevention and early intervention research that aligns with NSW Health priorities. The objectives of the PRSP are to: increase high-quality and internationally recognised prevention research in NSW; support the generation of research evidence that addresses NSW Health prevention priorities, including cross-government priorities; encourage the adoption of research evidence in relevant policies, programs and services in NSW; and build the prevention research capability of NSW Health staff and the NSW Health system. Methods: Funding recipients provide information about their research, translation and capability building achievements in their funding applications and submit annual progress reports. Data from these sources were aggregated to illustrate trends in indicators of research excellence over time. Prior to the most recent call for applications, the program was reviewed. The review included consultations with funding recipients, policy and practice partners, and key funding stakeholders. Stakeholders' perceptions of the benefits and challenges associated with the PRSP were drawn from the consultation data. Results: PRSP funding recipients demonstrate considerable increases over time on several indicators of research excellence, including peer-reviewed journal publications, grant income, and research students supervised. Recipients use a range of strategies to ensure dialogue with health system partners, and report research impacts at the local, state, national and international levels. PRSP funding also supports the development of research capability. Lessons learnt: The PRSP is a unique scheme that is highly valued by both funding recipients and health system stakeholders. The continuity of funding provided under the scheme enables recipients to adopt a strategic approach to their research and develop innovative strategies to support its conduct and use.